431 - Rôle de l’IICA en tant qu’organisme d’exécution des programmes et des projets de la Banque Interaméricaine de Développement (BID) - Conseil Interaméricain de l'agriculture (CIA) (2017)
(WD-317) Proposal for strengthening IICA´s role as an executing agency for agricultural and rural development projects and programs within the framework of the new IDB policy